2012
DOI: 10.1002/sia.4825
|View full text |Cite
|
Sign up to set email alerts
|

X‐ray photoelectron spectroscopy and time‐of‐flight secondary ion mass spectrometry characterization of aging effects on the mineral fibers treated with aminopropylsilane and quaternary ammonium compounds

Abstract: X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry were used to investigate the aging effects on the aminopropylsilane (APS) and quaternary ammonium surfactant-treated mineral fibers. APS-coated mineral fiber samples were treated with cationic surfactant and mineral oil and aged at 70 C temperature and 95% humidity. From quantitative XPS measurements, an increase in the atomic composition of oxygen, nitrogen, and silicon is observed after aging. An increase in the protona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…One of the critical issues in using APS in industrial applications is the degradation of the layer properties under high humidity and temperature. Therefore, the stability of APS layers has been well-studied, ,,, and hydrolysis of Si–O–Si bonds is accepted as one of the main mechanisms for APS layer decomposition. In this work, we formed APS layers by deposition from aqueous and organic solutions on surfaces of model silica, mineral fiber melt wafers, and mineral fibers that more closely reflect the processes used in industry.…”
Section: Introductionmentioning
confidence: 99%
“…One of the critical issues in using APS in industrial applications is the degradation of the layer properties under high humidity and temperature. Therefore, the stability of APS layers has been well-studied, ,,, and hydrolysis of Si–O–Si bonds is accepted as one of the main mechanisms for APS layer decomposition. In this work, we formed APS layers by deposition from aqueous and organic solutions on surfaces of model silica, mineral fiber melt wafers, and mineral fibers that more closely reflect the processes used in industry.…”
Section: Introductionmentioning
confidence: 99%
“…If detachment of PUF was caused by decomposition of bonds only between PUF and APS, which M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 23 would leave APS molecules on fiber surfaces, the IEP would shift to high pH because of APS basic amino groups. Previously, it was shown that APS coupling agent layers are not stable under the ageing conditions used in this study 12,13 . Figure 8.…”
Section: Accepted Manuscriptmentioning
confidence: 65%
“…In the case of mineral wool production, 3-aminopropylsilane (APS) coupling agent is used to enhance PUF adhesion to the mineral fiber surfaces 2 . APS reacts with mineral wool 12,13 or glass fiber [14][15][16][17][18][19][20][21] surface through silanol groups, -Si(OH) 3 , and with the polymer matrix 22 through its amino group -NH 2. This allows binding of mineral fibers together ( Figure 1) and creates the necessary mechanical properties for the mineral wool product, when the PUF binder is cured 2 . However, reactions between the silanol group of APS and polymer matrix have also been described [23][24][25] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…A comparison of the N 1s spectra of wheat straw with those of N 2 -300–N 2 -800 biochars clearly indicates a change in nitrogen compounds during pyrolysis. Nitrogen in wheat straw exists mainly in four forms: alkaloid-N with a binding energy of 398.6 eV, free amino acid-N with a binding energy of 399.2 eV, protein-N with a binding energy of 399.7 eV, and NH 4 + -N with a binding energy of 401.3 ± 0.4 eV . Protein-N is the dominant species (highest content; 39240 mg/kg).…”
Section: Resultsmentioning
confidence: 99%